Pengaruh Inflasi dan Suku Bunga Terhadap Nilai Tukar Negara-Negara Regional ASEAN - Wisnu Jaya Lutfiansyah; Sri Indah Nikensari; Puji Yuniarti (Teewan Journal Solutions, 2026)
The exchange rate is the amount of domestic currency that must be paid to acquire one unit of foreign currency. This refers to recent changes in exchange rates. Changes in exchange rates are influenced by many factors, such as inflation and interest rates, which are related to changes in a country's currency exchange rate. This study analyzes the effect of inflation and interest rates on the exchange rates of ASEAN regional countries. Data was collected from the period before and after the peak of the pandemic, from 2019 to 2024, to observe the short- to medium-term impacts. The results show that inflation is negatively related to exchange rates, with increased domestic inflation causing currency depreciation. Meanwhile, interest rates exhibit varying effects depending on each country's monetary policy. This study concludes that, in the context of economic mapping in ASEAN regional countries over the past five years, policies focused on managing and controlling inflation are more effective in maintaining exchange rate stability than interest rate adjustments.